The Effect of Competence, Work Motivation and Organizational Culture on Employee Performance at PT. Permodalan Nasional Madani Medan Branch Office - Ilham Pinayungan Siagian; Adi Susilo Jahja (Formosa Journal of Applied Sciences, 2024)
The focus of this research is on PT. Permodalan Nasional Madani Medan Branch Office, using three independent variables, namely competence, work motivation and organizational culture. The sample consists of all 100 employees of PT. Permodalan Nasional Madani Medan Branch Office, selected by census. The data analyzed came from questionnaires distributed to all employees sampled in this research. The analysis method in this research uses SEM analysis with SmartPLS software. Based on the research results, it shows that competence has a positive and significant effect on employee performance. Apart from that, work motivation has a positive and significant effect on employee performance. Meanwhile, organizational culture has a positive and significant effect on employee performance.